The effect of unemployment toward GDP per capita and economic growth indicators in Southeast Asia developing countries / Mohamad Rahmat Susianto - Susianto, Mohamad Rahmat (2018)
In this paper has investigate the relationship between unemployment and GDP per capita alongside with economic indicators in Southeast Asia Developing Countries. In this study, the independent variables is unemployment, inflation, consumption, and population, while the dependent variables are gross domestic production per capita, foreign direct investment, and saving. This study use panel data consist of 10 years between 12006 to 2015 and use 10 selected Southeast Asia countries were modelled into multiple regression model.